Acute and Chronic Exercise Effects on Human Memory: What We Know and Where to Go from Here - Paul D. Loprinzi (MDPI AG, 2021)
Although the acquisition, storage, and retrieval of memories was once thought to happen within a single memory system with multiple processes operating on it, it is now believed that memory is comprised of both distinct and interacting brain systems [...]